Fast formation of a supramolecular ion gel/solvoplastic elastomer with excellent stretchability - Bai, Shishun (R Soc Open Sci, 2018)
This study describes a simple yet efficient approach for the preparation of an ionic gel that is also elastomeric in its solid-state bulk form. A series of poly(2-(diethylamino)ethyl methacrylate-co-lauryl methacrylate) P(DMAEMA-co-LMA) copolymers were synthesized first by radical polymerization. Quaternization of the PDMAEMA component in tetrahydrofuran enables the formation of supramolecular network, giving rise to an ion gel. An elastomer with an elongation at break of over 600% was obtained from the gel. The elastomer, connected by supramolecular ionic cross-links, is solvoplastic in certain solvents. The simple yet efficient approach of the formation of ion-gel and the dried elastomer allows fast preparation of both gel-like and solid-state elastic materials for various applications where recyclability is required.